APPLIED ASPECTS OF THE ANALYSIS OF BUSINESS ACTIVITY OF THE ENTERPRISE - CHUY, Iiryna; SHEMCHUK, L.; BODNARIUK, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The purpose of the article is to researchthe theoretical and methodological foundations of the process of assessing the business activity of an enterprise, to analyze the indicators of business activity of an enterprise and assess its level, to identify its impact on financial stability and profitability, to determine ways and reserves to strengthen the level of business activity of the enterprise.The main purpose of analyzing the enterprise’s business activity is to make effective management decisions to ensure sustainable development and increase its’s competitiveness in a market environment. The article explores the applied aspects of the business activity of the enterprise, reveals its characteristic features. The indicators that evaluate the business activity of the enterprise and the features of their application are determined. The analysis of compliance with the enterprise’s"golden rule of economics, comparison of the state of receivables and payables,he operating cycle turnover and duration and its components of PJSC "Lviv confectionery factory "Svitoch" are carried out.The analysis confirmed a slowdown in the progressive development of the company and a decrease in the level of its business activity: only in 2018 there is a high level of business activity of the studied enterprise; the level of business activity is low during 2019-2020. There is a steady trend for the assets accumulation and for decreasing the level of financial stability during the analyzed years, the increase in equity exceeded the increase in invested capital into assets by 8.3% butcaused the decreasing in the level of profitability of sales of products.The duration of the operating cycle decreased from 144.2 days in 2018 to 135.9 days in 2020 due to the fact that the turnover of tangible elements of current assets and receivables accelerated. This led to the release of working capital in the amount of UAH 59.3 million in 2020. The main directions forincreasingthe business activity of PJSC"Svitoch" can be:increasing in inventory turnover ratios, receivables, work in progress, improving the state of settlements with debtors, in particular by introducing advance payments for goodsand strict control over the level of settlements and payment discipline for all participants in economic relations.